Infrared aircraft measurements of stratospheric composition over Antarctica during September 1987 - Farmer, C. B.; Schaper, P. W.; Lowes, L. L.; Toon, Goeff C.; Blavier, J.-F.; Norton, R. H. (1988)
The JPL Mark IV interferometer recorded high resolution, infared solar spectra from the NASA DC-8 aircraft during flights over Antarctica in September 1987. The atmospheric absorption features in these spectra were analyzed to determine the overburdens of O3, NO, NO2, HNO3, ClONO2, HCl, HF, CH4, N2O, CO, H2O and CFC-12. The spectra were obtained at latitudes which ranged between 64 degrees S and 86 degrees S, allowing the composition in the interior of the polar vortex to be compared with that at the edge. The latitude dependence observed for NO, HO2, HNO3, ClONO2, HCl and HF are summerized. The values at 30 deg S were observed on the ferry flight from New Zealand to Hawaii. The dashed lines connecting the two were interpolated across the region for which there are no measurements. The chemically perturbed region is seen to consist of a collar of high HNO3 and ClONO2 surrounding a core in which the overburdens of these and of HCl and NO2 are very low. Clear increases in the overburdens of HF and HNO3 were observed during the course of September in the vortex core. HCl and NO2 exhibited smaller, less significant increases. The overburdens of the tropospheric source gases, N2O, CH4, CF2Cl2, and H2O were observed to much smaller over Antarctica than at mid-latitudes. This, together with the fact that HF over Antarctica was more that double its mid-latitude value, suggests that downwelling has occurred.